Communication Between Gamers in the Mobile Legends Bang Bang Online Game Group (Qualitative Descriptive Study of the WWE Company Mobile Legends Online Game Community) - Alifian Muhammad Rahmawan Firdaus; Nur Maghfirah Aesthetika (Universitas Muhammadiyah Sidoarjo, 2023)
This qualitative research investigates the dynamics of group communication within the online game Mobile Legends: Bang Bang. The study aims to explore how effective communication and positive interactions among players can be fostered within the game, resulting in mutual understanding and cooperation. Employing a case study approach, the researcher conducted interviews with five Mobile Legends: Bang Bang players. Drawing on Laswell's communication theory, which encompasses the elements of who, says what, through which media, to whom, and with what effects, the study highlights the online communication capabilities provided by the game, such as chat and voice note features. Through these features, players can engage in effective online communication without the need for physical meetings. The research findings reveal that Mobile Legends: Bang Bang facilitates the formation of communities, allowing players to establish connections and build relationships beyond the game. The study concludes that despite the presence of in-game noise, the communication among gamers within a group is highly effective, with players predominantly utilizing chat features and symbols during gameplay for efficient communication. After each match, players further engage in voice chat discussions to analyze game outcomes and address challenges faced during gameplay. This research sheds light on the significance of effective communication in online gaming communities and highlights the potential for building strong player connections and fostering positive interactions in virtual environments Highlights: Effective communication: The study highlights the importance of effective communication in fostering collaboration and understanding among players in the online game Mobile Legends: Bang Bang. Communication tools: The research identifies the significance of chat features and voice chat in facilitating communication and coordination during gameplay and post-match discussions. Building connections: The findings emphasize the potential of online gaming communities, such as Mobile Legends: Bang Bang, in enabling players to form relationships and establish connections beyond the virtual environment, enhancing the overall gaming experience. Keywords: Group communication, Online gaming, Mobile Legends: Bang Bang, Chat features, Voice chat